ҚАРАҚАЛПАҚ ҲӘМ ИНГЛИС ТИЛЛЕРИНДЕ АТАЎЫШ СӨЗ ШАҚАПЛАРЫНЫҢ СЕПЛИК КАТЕГОРИЯСЫ ҲАҚҚЫНДА - Отарбаева, Р.; Утепбергенова, Д. (ILIM hám JÁMIYET, 2018)
The article deals with the problems of declension of nominative parts of speech in the English and Karakalpak languages in the comparative aspect. The authors scientifically found out such grammatical means which make it conducive to decline different parts of speech in these two compared languages. It’s revealed in the article those and other specific and common grammatical rules and the ways of their realization in the practice of written and oral communication.